2005
DOI: 10.1667/rr3420
|View full text |Cite
|
Sign up to set email alerts
|

Role of Homologous Recombination in the Alpha-Particle-Induced Bystander Effect for Sister Chromatid Exchanges and Chromosomal Aberrations

Abstract: The bystander effect for sister chromatid exchanges (SCEs) and chromosomal aberrations was examined in hamster cell lines deficient in either DNA-PKcs (V3 cells, deficient in nonhomologous end joining, NHEJ) or RAD51C (irs3 cells, deficient in homologous recombination, HR). Cells synchronized in G0/G1 phase were irradiated with very low fluences of alpha particles such that < 1% of the nuclei were traversed by an alpha particle. Wild-type cells showed a prominent bystander response for SCE induction; an even g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 22 publications
4
36
0
Order By: Relevance
“…ATM is reported to play a role in telomere maintenance as well (Pandita, 2002;Denchi and de Lange, 2007). In addition to DNA-PKcs and ATM's well-established roles in repair and intracellular signaling, (Nagasawa et al, 2003(Nagasawa et al, , 2005Collis et al, 2005;Lavin and Kozlov, 2007), our findings indicate a role for these proteins in intercellular signaling of the ionizing radiation-induced BSE. We designed a cell transfer strategy that enables us to differentiate between the generation versus the reception of bystander signals.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…ATM is reported to play a role in telomere maintenance as well (Pandita, 2002;Denchi and de Lange, 2007). In addition to DNA-PKcs and ATM's well-established roles in repair and intracellular signaling, (Nagasawa et al, 2003(Nagasawa et al, , 2005Collis et al, 2005;Lavin and Kozlov, 2007), our findings indicate a role for these proteins in intercellular signaling of the ionizing radiation-induced BSE. We designed a cell transfer strategy that enables us to differentiate between the generation versus the reception of bystander signals.…”
Section: Discussionmentioning
confidence: 56%
“…Given that the multiple markers that have been used to study the BSE, that is, micronuclei formation (Yang et al, 2007), clonogenic survival (O'NeillMehlenbacher et al, 2007), apoptosis (Grifalconi et al, 2007) and sister chromatid exchange (SCE) (Nagasawa et al, 2005) (Figure 1), are themselves considered to be detrimental, it has been assumed that the BSE is harmful to neighboring cells. However, it has also been proposed that the BSE may actually be beneficial at a tissue level; cells exposed to a bystander signal are more radioresistant to subsequent IR-induced damage indicative of an adaptive response (Iyer and Lehnert, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously we reported that spontaneous SCE frequencies for the V79-derived rad51c cell line irs3 were 0.16 SCE per chromosome, approximately 50% lower than wild-type V79 cells [23]. Following irradiation with very low doses of α-particles (<2.6 mGy, <2% of cells directly hit), SCEs were not significantly increased above background levels in irs3 cells whereas SCE frequencies increased significantly 30-40% above background in both wild-type V79 and non-homologous end joining (NHEJ)-deficient V3 (deficient in DNA-PKcs) CHO cells.…”
Section: Introductionmentioning
confidence: 85%
“…In addition, mainly chromatid-type aberrations were induced in the bystander cells (i.e., cells neighboring directly-irradiated cells) when cultures of V79, V-3, and xrs5 (deficient in Ku70/80) cells were irradiated in G0/G1-phase, which suggested increased levels of single-stranded DNA damage in the bystander cells [23][24][25]. Similarly, the spectrum of hprt mutations induced in bystander cells following low dose α-particle irradiation were nearly all point mutations, in contrast to directly irradiated cells for which total and partial gene deletions predominated [26,27].…”
Section: Introductionmentioning
confidence: 99%